2017
DOI: 10.1016/j.matlet.2016.09.110
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature fabrication of hydrangea-like NiCo2S4 as electrode materials for high performance supercapacitors

Abstract: Hydrangea-like NiCo 2 S 4 as electrode materials for high performance supercapacitors was synthesized by using a facile low temperature (90 °C) two-step hydrothermal technique without surfactant or template. The special hydrangea-like structure and large specific surface area (74.8 m 2 /g) provided plenty of electro active sites which were beneficial to superior pseudocapacitive performance of NiCo 2 S 4 . The supercapacitors performance of NiCo 2 S 4 was investigated by a three-electrode system. NiCo 2 S 4 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The specific capacitance determined from the GCD curves is presented in Figure c. The maximum specific capacitances of NCS hexagonal plates and NiCo−OH NPs are 833, 680, 550, 466, 375, 350, 333 mF cm −2 and 733, 560, 500, 433, 350, 266 mF cm −2 at 10, 12, 15, 20, 30 and 40 mA cm −2 , respectively, which are higher than the previously reported . A steady decrease in specific capacitance with increasing current densities from 10 to 40 mA cm −2 is mainly due to the time constraints on the interaction between the electrode and electrolyte ions during charge/discharge process.…”
Section: Supercapacitor Properties Of the Electrodesmentioning
confidence: 77%
“…The specific capacitance determined from the GCD curves is presented in Figure c. The maximum specific capacitances of NCS hexagonal plates and NiCo−OH NPs are 833, 680, 550, 466, 375, 350, 333 mF cm −2 and 733, 560, 500, 433, 350, 266 mF cm −2 at 10, 12, 15, 20, 30 and 40 mA cm −2 , respectively, which are higher than the previously reported . A steady decrease in specific capacitance with increasing current densities from 10 to 40 mA cm −2 is mainly due to the time constraints on the interaction between the electrode and electrolyte ions during charge/discharge process.…”
Section: Supercapacitor Properties Of the Electrodesmentioning
confidence: 77%
“…Reproduced with permission. [112] Copyright2 016,Elsevier.Low-(f) and high-magnification (g) SEM images and EDX (h) results for amaryllis-like NCS nanoflowers. Reproduced with permission.…”
Section: Three-dimensional Ncsmentioning
confidence: 99%
“…Zhao et al synthesized hydrangea-like NCS (Figure 6e)a s electrode materials for SCs by using al ow-temperature (90 8C), two-steph ydrothermalt echnique without surfactant or templates. [112] The special hydrangea-like structure and large specific surface area (74.8 m 2 g À1 )p rovided plenty of electroactive sites that were beneficial to the superior pseudocapacitive performance of NCS. NCS exhibited as pecific capacitance of 1475 Fg À1 at ac urrent density of 3Ag À1 ,a nd af airly high rate capacityo f1 152 Fg À1 at 20 Ag À1 .…”
Section: Three-dimensional Ncsmentioning
confidence: 99%
“…Therefore, taking reduced graphene oxide as a framework is an effective way to reinforce the mechanical strengths of the composites. Nickel-cobalt sulfide is one of the most promising one among various pseudocapacitor electrode materials, such as metal oxides, metal sulfides, and conductive polymers (Jinlong et al, 2017;Wen et al, 2017;Zhao et al, 2017;Liang et al, 2018). Although, there is some doubt about the definition of pseudocapacitance (Brousse, 2015;Jiang and Liu, 2019), many studies reported that transition metal sulfides were classified as one kind of pseudocapacitive materials (Xiong et al, 2015;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%